Translational Genomics to Develop a Salmonella enterica Serovar Paratyphi A Multiplex Polymerase Chain Reaction Assay - Ou, Hong Yu; Ju, C.T.S.; Thong, Kwai Lin; Ahmad, Norazah; Deng, Z.X.; Barer, Michael R.; Rajakumar, Kumar (Elsevier, 2007)
The use of pathogen genome sequence data for the control and management of infections remains an ongoing challenge. We describe a broadly applicable, web-enabled approach that can be used to develop bacteria-specific polymerase chain reaction (PCR) assays. Salmonella enterica Paratyphi A has emerged as a major cause of enteric fever in Asia. Culture-based diagnosis is slow and frequently negative in patients with suspected typhoid and paratyphoid fever, potentially compromising patient management and public health. We used the MobilomeFINDER web-server to perform in silico subtractive hybridization, thus identifying 43 protein-coding sequences (CDSs) that were present in two Paratyphi A strains but not in other sequenced Salmonella genomes. After exclusion of 29 CDSs found to be variably present in Paratyphi A strains by microarray hybridization and grouping of remaining CDSs by genomic location, four dispersed targets (stkF, spa2473, spa2539, hsdM) were used to develop a highly discriminatory multiplex PCR assay. All 52 Paratyphi A strains within the diverse panel investigated produced one of two pathognomonic four-band signatures. Given rapid and ongoing expansion of DNA and comparative genomics databases, our universally accessible web-server-supported do-it-yourself approach offers the potential to contribute significantly to the rapid development of species-, serovar-, or pathotype-specific PCR assays targeting pre-existing and emerging bacterial pathogens.